A study to assess impact of carbon credit trading into costs and prices of different goods and services - a study from the airline industry. (12th September 2019) - Shrivastava, Neharika; Sharma, Vandna; Chaklader, Barnali
Global climate change has compelled companies to revamp their existing business practices. Increases in CO2 can only be offset by reforestation or increases in water bodies. The present study of Indian airlines is an attempt to prove how CO2 emissions can be offset with only a marginal impact on the price of a product or service. When booking air tickets online, passengers can choose to offset CO2 emissions. The objective of this paper is to study the willingness of air travellers to pay for carbon offsetting and the impact of such payments on ticket price. A questionnaire to measure willingness (using a five-point Likert scale) was sent to 150 air passengers booking tickets through makemytrip.com using judgemental and convenience sampling. Of these, 100 responses were received. Statistical analysis was conducted using a Z-test. While the impact on ticket price ranged from just 1.00% to 1.07%, CO2 emissions were offset from 44% to 200%. From the survey, 44% of respondents agreed and 25% strongly agreed that they did not mind paying for carbon sequestration while booking tickets and the amount they were willing to pay ranged from Rs. 44 to Rs. 121.